A filosofia do corpo, vontade e representação em Arthur Schopenhauer - Rosato, Gustavo Rodrigues (2018)
The present text aims to reflect about the theories of body, Will and representation in Arthur Schopenhauer and how body and Will influence the realization of the world as representation. In this regard, each of these subjects should be deepened, starting with the theory of knowledge in Schopenhauer and Kant on judgments and representations; followed by observations on the divergence between Kant and Schopenhauer, differentiating the thing in itself from the Will; and finally the world’s knowledge to Schopenhauer by the perspective among body, representation and Will. The work that underlies the formulations, and which mainly motivates this work, is The World as Will and Representation, published in 1818 by Arthur Schopenhauer (1788-1860). From the basic concepts of this work – body, Will and representation –, a re-reading of the predecessors that influenced the Schopenhauer’s thought in the composition of them is necessary. In the preface to the first edition of The World as Will and as Representation, Schopenhauer clearly indicates as a requirement to the reader the knowledge of Kantian philosophy and affirms that this is the starting point for the formulation of his work, especially when it comes to the definitions of subject and object. Furthermore, two Kantian definitions are fundamental in this analysis – noumenon (thing in itself) and phenomenon (apparition) –, since they are determinants in the relations proposed by Schopenhauer among Will, body and world as representation. It is intended to emphasize how Schopenhauer develops his theory about the body, according to the importance of the concept of body for the formulation of his theories of knowledge, metaphysics and aesthetics.